A phase 1, randomized, controlled dose-escalation study of EP-1300 polyepitope DNA vaccine against Plasmodium falciparum malaria administered via electroporation. Issue 46 (4th November 2016) - Spearman, Paul; Mulligan, Mark; Anderson, Evan J.; Shane, Andi L.; Stephens, Kathy; Gibson, Theda; Hartwell, Brooke; Hannaman, Drew; Watson, Nora L.; Singh, Karnail
Abstract: Plasmodium falciparum malaria is one of the leading infectious causes of childhood mortality in Africa. EP-1300 is a polyepitope plasmid DNA vaccine expressing 38 cytotoxic T cell epitopes and 16 helper T cell epitopes derived from P. falciparum antigens expressed predominantly in the liver phase of the parasite's life cycle. We performed a phase 1 randomized, placebo-controlled, dose escalation clinical trial of the EP-1300 DNA vaccine administered via electroporation using the TriGrid Delivery System device (Ichor Medical Systems). Although the delivery of the EP-1300 DNA vaccine via electroporation was safe, tolerability was less than that usually observed with standard needle and syringe intramuscular administration. This was primarily due to acute local discomfort at the administration site during electroporation. Despite the use of electroporation, the vaccine was poorly immunogenic. The reasons for the poor immunogenicity of this polyepitope DNA vaccine remain uncertain. Clinical Trials Registration: ClinicalTrials.gov NCT01169077.